What Kind of Ethical Education will Serve our Future Needs? (Analytic Teaching, 1996)
Introduction: People tend to ask us: What kind of knowledge and skills will our young generation need in the future? The obvious answer is: Skills of learning and thinking! Schools must be learning centres where we all study the skills of learning and are seekers of knowledge. But what does this mean if we think of ethics and, in particular, of ethical instruction in formal education? What sorts of skills in ethics does a good life call for in our modern, or perhaps, in our post modern condition?